Increasing economic burden of tyrosine kinase inhibitor treatment failure by line of therapy in chronic myeloid leukemia. (1st February 2016) - McGarry, Lisa J.; Chen, Yaozhu J.; Divino, Victoria; Pokras, Shibani; Taylor, Catherine R.; Munakata, Julie; Nieset, Christopher C.; Huang, Hui; Jabbour, Elias; Malone, Daniel C.
Abstract: Objective: To assess the economic burden of tyrosine kinase inhibitor (TKI) treatment failure in chronic myeloid leukemia (CML), by assessing all-cause health care resource use (HCRU) and costs in the year after treatment failure by line of therapy (LOT; 1L/2L/3L) using real-world data. Methods: Treatment episodes initiating a TKI of interest (index TKI) during June 2008–December 2011 were identified from the IMS PharMetrics Plus Health Plan Claims Database for adult patients with CML diagnosis (ICD-9-CM 205.1x), 120 days pre-index continuous enrollment (CE) and no clinical trial participation. Episodes experiencing treatment failure, defined as switch to a non-index TKI or discontinuation of index TKI (gap of ≥ 60 days), and with 1 year CE post-failure, were analyzed. LOT was determined by number of unique TKIs used in the pre-index. All-cause HCRU and costs (2012 USD) in the 1 year post-failure were assessed by LOT, and the comparisons between 1L and 2L failures were also adjusted using multivariate generalized linear models (GLMs) to control for underlying differences. Results: A total of 706 episodes were identified (518 1L; 180 2L; 8 3L). Unadjusted HCRU over 1 year post-failure increased significantly. This was accompanied by a significant increase in unadjusted mean costs for 2L failures vs. 1L failures ($99, 624 vs. $78, 667, p  = 0.021, Δ$20, 957). Following the adjustment using GLMs, adjusted mean costs were 38% higher (95% CI 1.14–1.68), driven primarily by use of medical services. In adjusted analyses, compared to 1L, 2L failures had: 45% more ambulatory visits (mean 31 vs. 21, 95% CI 1.26–1.66), 75% higher risk of hospitalization (33% vs. 23% hospitalized, 95% CI 1.16–2.64), and 73% higher medical costs (95% CI 1.31–2.29). Medical costs comprised a greater proportion of total costs in 2L vs. 1L (55% vs. 44%); pharmacy costs did not increase significantly. Conclusions: The economic burden over 1 year post TKI failure increased with each sequential line of TKI treatment failure.